2019
DOI: 10.4236/ojgas.2019.98018
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Serological Profile of Hepatitis B Virus in an Urban Area in Mali

Abstract: The objective of our study was to evaluate hepatitis B virus (HBV) infection in an urban population. This longitudinal study was conducted in Bamako District and Kati Commune. After a preparatory phase, the persons who accepted the protocol were assessed for HBsAg. HBsAg carriers had blood collection for HBeAg assay, viral load assessment, genotyping, DNA mutation testing, and severity of hepatic fibrosis and necrosis. At the end of this study, 1475 persons were included, of which 195 had HBsAg positive confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…This frequency of HBV infection in our context is reported by a previous study which found at least one serum marker of HBV in 60.2% of patients with HCC [9]. A study recent report has reported the prevalence of HBs Antigen to be 14.7% of the general population [7]. A recent study reported the prevalence of the HBs Antigen to 14.7% of the general population [7].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This frequency of HBV infection in our context is reported by a previous study which found at least one serum marker of HBV in 60.2% of patients with HCC [9]. A study recent report has reported the prevalence of HBs Antigen to be 14.7% of the general population [7]. A recent study reported the prevalence of the HBs Antigen to 14.7% of the general population [7].…”
Section: Discussionsupporting
confidence: 81%
“…The sex ratio was 1.73 in our study, which was contrary to that found by Hachicha et al [6] which was 0.44. This difference could be explained by the frequency of chronic HBV carriage in humans in our [7]. The predominance of cytolysis in farmers and housewives were reported by our study.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation